« Ils sont comme nous » : Les revues francophones belges et la Flandre (1919-1939) Pour une approche macro- et microsociologique combinée - Reine Meylaerts (Contextes)
The present article wants to provide some methodological reflections for the study of periodicals and their role in literary dynamics. It draws on existing field theoretical and discourse analytical models on the one hand (macro-sociological level) and combines them on the other hand (micro-sociological level) with new insights concerning the individual as a sociological construct and the complex relationships between structure (the periodical) and actor (the collaborator). The article illustrates these reflections with a case study on discourse on Flemish literature and Belgian identity in francophone Belgian periodicals (1919-1939) from a macro- and micro-sociological perspective.